If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = 6(6m + -7) + -6 Reorder the terms: 60 = 6(-7 + 6m) + -6 60 = (-7 * 6 + 6m * 6) + -6 60 = (-42 + 36m) + -6 Reorder the terms: 60 = -42 + -6 + 36m Combine like terms: -42 + -6 = -48 60 = -48 + 36m Solving 60 = -48 + 36m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-36m' to each side of the equation. 60 + -36m = -48 + 36m + -36m Combine like terms: 36m + -36m = 0 60 + -36m = -48 + 0 60 + -36m = -48 Add '-60' to each side of the equation. 60 + -60 + -36m = -48 + -60 Combine like terms: 60 + -60 = 0 0 + -36m = -48 + -60 -36m = -48 + -60 Combine like terms: -48 + -60 = -108 -36m = -108 Divide each side by '-36'. m = 3 Simplifying m = 3
| -4(3n-4)=-56 | | -25=-1-6(1+3x) | | k^3=144k | | -7(1+3p)=-70 | | 10x^2+40x+2=0 | | 8x^3+64=0 | | 3(2n+4)+5(3-2n)=7-2n | | -2=-7(4a+7) | | 3(2+5x)=-39 | | 6(8k+8)=0 | | 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 | | 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 | | 10x-26=264 |